FOOD INDUCTRY PRODUCTION PROGRAMME MANAGEMENT CHARACTERISTICS - DANYLIUK, VIACHESLAV; KOSTROMIN, A. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Production programme is an important part of the business plan of every business organization. It must represent a composition of product range, quality and quantity of manufactured products. Business organization`s management can effectively allocate resources between different areas of activities and get the maximum economic effect from the sale of goods and services, because of correct production programme. Business organization will get additional benefits in the market competition with production program. The problem of forming a production program is especially relevant for business organizations of the food industry. Products in this area have a short shelf life. The key issues on the way to effective market functioning are understanding the required production volumes and the number of required resources. The aim of the research is to explore features typical for management of food industry business organizations production programme. This article explores the essence of the concept of "production program". A critical analysis of previous publications and sources, which were written by Ukrainian and foreign researchers are given. After analysis we provided our own definition of "production programme". Also we investigated features of formation of the production programme. Algorithms of formation of the production program and requirements to its formation are given. Features of activity of the enterprises of the food industry and influence of these features on formation of production programs of the business organizations of this branch are resulted. Also methods of marketing research were researched and given in the article. Three methods of production programme optimization were given according to defined features of food industry business organizations.